Heat-conducting composite material based on laser-induced graphene and preparation method of heat-conducting composite material
By using the forest-like and flesh-like zone structure of the laser-induced graphene layer in the thermally conductive composite material and filling the phase change material PEG, the problems of low light absorption, photothermal conversion and energy storage efficiency in the prior art are solved, and more efficient thermal management and component protection are achieved.
Patent Information
- Application Number
- CN202510011028.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
Existing thermally conductive composite materials based on laser-induced graphene cannot have super high light absorption and photothermal conversion at the same time, and have low energy storage efficiency, which affects the life and mechanical stability of components.
The structure of a resin support layer and a graphene layer is adopted, where the graphene layer forms forest-like and flesh-like regions through laser induced processing, fills with phase change material PEG, and adjusts laser parameters to optimize the microstructure and fill density of graphene.
On the basis of maintaining high light absorption, the photothermal conversion rate is improved, the temperature stability is ensured, components are protected, energy storage efficiency is enhanced, and the complexity of the preparation process is reduced.
Smart Images

Figure CN119798754A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of graphene preparation and application, in particular to a thermally conductive composite material based on laser-induced graphene and a preparation method thereof. Background Art
[0002] With the continuous advancement of science and technology and the improvement of people's living standards, the miniaturization, high integration and high performance of electronic equipment have developed rapidly, making thermal management issues increasingly prominent. The development of new high-performance photothermal devices has become a top priority.
[0003] The structures of existing thermal conductive materials based on laser-induced graphene are mainly the following: first, planar structure, laser-induced graphene is directly formed on a polyimide substrate, usually a two-dimensional honeycomb structure, with high light absorption capacity, can fully exchange heat with the surrounding environment, and relatively high light-to-heat conversion efficiency, but rapid temperature rise and fall will have a great impact on the life of components; second, composite three-dimensional structure, using physical mixing, chemical deposition and other methods to composite and fill laser-induced graphene with other materials such as metals. Although its photothermal performance in the direction perpendicular to the film is improved compared with the two-dimensional planar structure, the preparation process is complicated, the cost is high, and its mechanical stability needs to be improved. In short, the existing thermal conductive composite materials based on laser-induced graphene cannot have excellent light absorption rate and light-to-heat conversion rate at the same time, and the energy storage and utilization efficiency is insufficient, there is no effective protection of components, and the mechanical stability is insufficient.
[0004] Literature points out that in nature, the topological distribution of leaves, plants, and branches in forest communities enables the entire community to have an ultra-high light energy utilization rate. Inspired by the natural light-to-heat conversion principle and thermal energy storage structure in leaves, the veins provide rapid energy collection and thermal energy transportation, and the loose structure of the mesophyll can achieve excellent heat storage function. The phase change material will maintain the temperature stability of its surrounding devices during the phase change process at different temperatures. Inspired by this, thermal conductive composite materials are further prepared to solve existing problems. Summary of the invention
[0005] In view of the above-mentioned defects, the purpose of the present invention is to propose a thermally conductive composite material based on laser-induced graphene to solve the problem that the current thermally conductive composite material based on laser-induced graphene cannot simultaneously have ultra-high light absorption rate and photothermal conversion rate, as well as low energy storage efficiency.
[0006] Another object of the present invention is to propose a method for preparing a thermally conductive composite material based on laser-induced graphene, reduce the complexity of the preparation process, ensure that the prepared thermally conductive composite material has the desired effect, and solve the problem of complex preparation process in the prior art.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] A thermally conductive composite material based on laser-induced graphene, comprising a resin support layer and a graphene layer, wherein the resin support layer is a polybenzoxazine film;
[0009] The graphene layer is obtained by laser induced processing on the resin support layer, the graphene layer includes a forest-like graphene region and a mesophyll-like graphene region, and the ratio of the area of the forest-like graphene region to the mesophyll-like graphene region is 1:3;
[0010] The forest-like graphene region and the mesophyll-like graphene region are each composed of a plurality of wedge-shaped partitions, and the wedge-shaped partitions of the forest-like graphene region and the wedge-shaped partitions of the mesophyll-like graphene region are distributed at intervals;
[0011] The graphene layer is filled with a phase change material, and the phase change material is PEG.
[0012] Furthermore, the forest-like graphene region and the mesophyll-like graphene region form a ring; and the wedge angle A of the wedge-shaped partition of the forest-like graphene region is 11.25°.
[0013] Preferably, the ratio of the thickness of the resin support layer to the thickness of the graphene layer is 7:3.
[0014] A method for preparing a thermally conductive composite material based on laser-induced graphene, which is used to prepare the above-mentioned thermally conductive composite material based on laser-induced graphene, comprises the following steps:
[0015] S1. Preparation of benzoxazine monomer: using a phenol source, an amine source and polyformaldehyde as raw materials, and xylene as a solvent, heating and stirring, synthesizing a benzoxazine monomer structure, and then using an organic solvent to help the benzoxazine monomer structure precipitate, and purifying to obtain a benzoxazine monomer; wherein the phenol source is one of bisphenol A and phenol, the amine source is 4,4'-diaminodiphenylmethane, and the organic solvent is one of petroleum ether, n-hexane and cyclohexane;
[0016] S2, preparing a polybenzoxazine film: melting and degassing a benzoxazine monomer to obtain a polybenzoxazine fluid, pouring the polybenzoxazine fluid into a glass mold, curing at high temperature, and demolding after cooling to obtain a polybenzoxazine film;
[0017] S3, laser induced processing: fix the polybenzoxazine film on the processing platform, use an ultraviolet laser, according to a preset pattern, laser induce the corresponding processing area on the polybenzoxazine film, and obtain the processed three-dimensional laser induced graphene;
[0018] The graph includes a forest-like region, a mesophyll-like region and a heat collection region; the forest-like graphene region corresponds to the forest-like region, and the mesophyll-like graphene region corresponds to the mesophyll-like region;
[0019] For the forest-like area, the laser power was set to 4 W, the laser scanning speed was set to 96 mm / s, and the laser scanning spacing was set to 0.01 mm; for the mesophyll-like area 2, the laser power was set to 5 W, the laser scanning speed was set to 77 mm / s, and the laser scanning spacing was set to 0.01 mm;
[0020] S4. Filling PEG: Immersing the processed three-dimensional laser-induced graphene into molten PEG, and after vacuum treatment, removing excess PEG on the surface to obtain a thermally conductive composite material based on laser-induced graphene.
[0021] Furthermore, in step S3, the polybenzoxazine film is subjected to laser induction, and the laser wavelength is set to 280-3500 nanometers and the defocus is 6 mm.
[0022] Preferably, in step S1, the phenol source is bisphenol A, and the molar mass ratio of bisphenol A: 4,4'-diaminodiphenylmethane: paraformaldehyde is (1-1.2): (0.8-1.2): (1-1.5);
[0023] The heating temperature was 120°C and the stirring time was 6 h.
[0024] Preferably, in step S2, the heating temperature for melting the benzoxazine monomer is 110° C., and the degassing time is 30 min.
[0025] Preferably, in step S2, the polybenzoxazine fluid is cured at high temperature, first at 180°C for 2 hours, then at 200°C for 2 hours, and finally at 220°C for 2 hours.
[0026] Preferably, in step S1, the step of purifying to obtain the benzoxazine monomer is:
[0027] A. Dissolving: dissolving the precipitated benzoxazine monomer structure in a solvent to obtain a solution containing the benzoxazine monomer; the solvent is one of ethyl acetate, dichloromethane and chloroform;
[0028] B. Washing: Wash the solution containing benzoxazine monomer three times with deionized water;
[0029] C. Drying: After the washed solution containing the benzoxazine monomer is dried using anhydrous sodium sulfate or anhydrous magnesium sulfate, a rotary evaporator is used to obtain the benzoxazine monomer.
[0030] Preferably, in step S4, the processed three-dimensional laser-induced graphene is immersed in molten PEG, the filling time is 2 hours, and the temperature is 90°C.
[0031] The technical solution provided by the present invention may include the following beneficial effects:
[0032] 1. Using different laser parameters for processing, the graphene has two microstructures, forest-like and plant leaf-like mesophyll. The forest-like graphene has a better light absorption rate. At the same time, the mesophyll-like graphene is set and filled with phase change material PEG. The ratio of the area to the forest-like graphene is 3:1. The combined effect can make the thermal conductive composite material have a better light-to-heat conversion rate while maintaining a high light absorption rate, while ensuring the temperature stability and effectively protecting the components that need heat collection.
[0033] 2. The complexity of the preparation process is reduced by preparing benzoxazine monomers, preparing polybenzoxazine films, laser-induced processing and filling phase change materials to prepare thermally conductive composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic structural diagram of an embodiment of the present invention.
[0035] Figure 2 It is a schematic diagram of the overall structure of an embodiment of the present invention.
[0036] Among them: forest-like area 1, mesophyll-like area 2, heat collection area 3, resin support layer 4, graphene layer 5. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0038] In order to facilitate the understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0039] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0040] The present invention proposes a thermally conductive composite material based on laser-induced graphene, comprising a resin support layer 4 and a graphene layer 5, wherein the resin support layer 4 is a polybenzoxazine film;
[0041] The graphene layer 5 is obtained by laser induced processing on the resin support layer 4, and the graphene layer 5 includes a forest-like graphene region and a mesophyll-like graphene region, and the ratio of the area of the forest-like graphene region to the mesophyll-like graphene region is 1:3;
[0042] The forest-like graphene region and the mesophyll-like graphene region are each composed of a plurality of wedge-shaped partitions, and the wedge-shaped partitions of the forest-like graphene region and the wedge-shaped partitions of the mesophyll-like graphene region are distributed at intervals;
[0043] The graphene layer 5 is filled with a phase change material, and the phase change material is PEG.
[0044] In order to solve the problems existing in the prior art, the distribution of leaves and plants in forest communities in nature is studied, and inspired by the natural light-heat conversion principle and thermal energy storage structure in leaves, this technical solution proposes a thermal conductive composite material based on laser-induced graphene, including a resin support layer 4 and a graphene layer 5. The resin support layer 4 is a polybenzoxazine film. Since the benzoxazine resin has a high residual carbon rate, it has excellent chemical stability and good mechanical properties. Three-dimensional porous graphene can be obtained by laser induction, which has the characteristics of easy processing and low cost. The graphene layer 5 is obtained by laser induction processing on the resin support layer 4, and the graphene layer 5 includes a forest-like graphene area and a mesophyll-like graphene area. The photosynthesis process of plant leaves is imitated. In plant leaves, there are generally two parts: veins and non-veins. The vein part is mainly for the transmission of nutrients, and the non-vein part is mainly for the utilization and storage of nutrients. The two parts work together to maximize the photosynthesis efficiency. Based on this design, the forest-like graphene area is equivalent to leaf veins, and its microstructure is similar to the distribution state of forest plants. In nature, in forest communities, incident light is reflected multiple times between trees and branches. Applying this principle to graphene can increase the light path and reflection opportunities, reduce direct reflection of light, enhance light absorption and transportation, and thus increase the light absorption rate of graphene; the microstructure of the mesophyll-like graphene area is similar to the mesophyll of plant leaves, with a large storage space, and works together with the forest-like graphene to increase the surface area. Graphene itself has excellent light-to-heat conversion performance, which can achieve the purpose of further improving the light-to-heat conversion rate while having a high light absorption rate.
[0045] At the same time, the graphene layer 5 is filled with phase change material. The energy storage and regulation of the thermally conductive composite material are mainly determined by the filled phase change material. The phase change material absorbs or releases a large amount of latent heat during the phase change process, and can maintain a relatively stable temperature for a certain period of time. When the ambient temperature rises, the phase change material begins to absorb heat and undergoes a phase change, such as from a solid state to a liquid state. The latent heat absorbed in this process can slow down the rate of temperature rise. When the ambient temperature drops, the phase change material releases latent heat and changes from a liquid state back to a solid state, thereby delaying the temperature drop and maintaining a relatively stable temperature. In addition, latent heat storage is a key mechanism for phase change materials to be used for energy storage. During the phase change process, the latent heat absorbed or released by the phase change material can be regarded as a storage and release process of energy. Since the phase change material can absorb or release a large amount of heat per unit mass during the phase change, this makes them have a high energy density in the energy storage system. The graphene in the mesophyll-like graphene area transfers the converted heat energy back to the forest-like graphene area, and at the same time stores another part of the converted heat energy into the phase change material, which facilitates the subsequent energy utilization and effectively promotes the photothermal conversion. It solves the problem in the prior art that the thermal conductive composite material based on laser-induced graphene cannot have excellent light absorption rate and photothermal conversion rate at the same time, and the energy storage efficiency is low.
[0046] In addition, the prepared thermally conductive composite material will be used for heat collection in photothermal elements. Phase change materials have the function of controlling the temperature balance of photothermal elements. Photothermal elements, especially heat collection devices, need to convert the collected light into heat as much as possible, so the temperature changes violently and the temperature difference is large, which has a great impact on the life of the components. After filling with phase change materials, since the phase change materials will undergo phase changes at different temperatures and absorb or release heat, they play a role in balancing and stabilizing the temperature of the components. In addition, the mesophyll-like graphene area has a large storage space, which is compatible with the needs of filling phase change materials. The two structures of graphene work together to solve the problems of low energy storage efficiency and component life of the current thermally conductive composite materials based on laser-induced graphene.
[0047] Furthermore, the ratio of the area of the forest-like graphene region to the mesophyll-like graphene region is 1:3. Under this ratio, the obtained thermally conductive composite material is ensured to have a high light absorption rate and a good light-to-heat conversion rate. The forest-like graphene region and the mesophyll-like graphene region are each divided into a plurality of wedge-shaped partitions. The thermal conductivity of the forest-like graphene is much higher than that of the mesophyll-like graphene, and is more suitable for the transfer of thermal energy. The slender wedge shape is suitable for transferring the thermal energy converted by the mesophyll-like graphene region to the desired position. The wedge-shaped partitions of the forest-like graphene area and the wedge-shaped partitions of the mesophyll-like graphene area are spaced apart, and the spaced-apart graphenes of different thermal conductivities guide the heat to the middle area. Due to the different thermal conductivities, thermal resistance is formed, thereby causing the heat flux to flow to a specific area, thereby manipulating the heat flow, further ensuring that the thermally conductive composite material based on laser-induced graphene of the technical solution has an excellent light-to-heat conversion rate while having a high light absorption rate, and can effectively protect components and improve energy storage efficiency.
[0048] In addition, the phase change material is PEG, i.e. polyethylene glycol, which has a much larger latent heat of phase change than other phase change materials, generally about 160 J / g. The larger the latent heat, the more energy the same mass of material can store or release, and the better the energy storage effect. Therefore, materials with large latent heat of phase change should be selected as much as possible to improve the storage and utilization efficiency of energy. Considering factors such as cost performance and output, PEG can have a large latent heat while meeting production needs and has a high cost performance.
[0049] Furthermore, the forest-like graphene region and the mesophyll-like graphene region form a ring, and the wedge angle A of the wedge-shaped partition of the forest-like graphene region is 11.25°.
[0050] Specifically, the forest-like graphene area and the mesophyll-like graphene area form a ring, and the device that needs to collect heat is arranged in the middle of the ring, which is conducive to transferring the converted heat energy to the central position.
[0051] The wedge angle A of the wedge partition of the forest-like graphene region is 11.25°, which is consistent with the area ratio of the forest-like graphene region to the mesophyll-like graphene region, that is, the forest-like graphene region is divided into eight parts, such as Figure 1 As shown, mesophyll-like graphene areas are distributed at intervals, and such a distribution further ensures that heat is better directed to the components in the middle.
[0052] Preferably, the thickness ratio of the resin support layer 4 to the graphene layer 5 is 7:3.
[0053] Specifically, the thickness ratio of the resin support layer 4 to the graphene layer 5 is 7:3. Due to the large difference in thermal conductivity between the resin support layer 4 and the graphene structure layer, thermal resistance will be formed at this ratio, effectively reducing heat loss, and the resin support layer 4 at this thickness ratio can further provide additional mechanical support and fire protection functions.
[0054] A method for preparing a thermally conductive composite material based on laser-induced graphene, which is used to prepare the above-mentioned thermally conductive composite material based on laser-induced graphene, comprises the following steps:
[0055] S1. Preparation of benzoxazine monomer: using a phenol source, an amine source and polyformaldehyde as raw materials, and xylene as a solvent, heating and stirring, synthesizing a benzoxazine monomer structure, and then using an organic solvent to help the benzoxazine monomer structure precipitate, and purifying to obtain a benzoxazine monomer; wherein the phenol source is one of bisphenol A and phenol, the amine source is 4,4'-diaminodiphenylmethane, and the organic solvent is one of petroleum ether, n-hexane and cyclohexane;
[0056] S2, preparing a polybenzoxazine film: melting and degassing a benzoxazine monomer to obtain a polybenzoxazine fluid, pouring the polybenzoxazine fluid into a glass mold, curing at high temperature, and demolding after cooling to obtain a polybenzoxazine film;
[0057] S3, laser induced processing: fix the polybenzoxazine film on the processing platform, use an ultraviolet laser, according to a preset pattern, laser induce the corresponding processing area on the polybenzoxazine film, and obtain the processed three-dimensional laser induced graphene;
[0058] The graph includes a forest-like region 1, a mesophyll-like region 2 and a heat collection region 3; the forest-like graphene region corresponds to the forest-like region, and the mesophyll-like graphene region corresponds to the mesophyll-like region;
[0059] For the forest-like region 1, the laser power was set to 4 W, the laser scanning speed was set to 96 mm / s, and the laser scanning spacing was set to 0.01 mm; for the mesophyll-like region 2, the laser power was set to 5 W, the laser scanning speed was set to 77 mm / s, and the laser scanning spacing was set to 0.01 mm;
[0060] S4. Filling PEG: Immersing the processed three-dimensional laser-induced graphene into molten PEG, and after vacuum treatment, removing excess PEG on the surface to obtain a thermally conductive composite material based on laser-induced graphene.
[0061] It is worth noting that the forest-like graphene area is located in the forest-like area 1, the mesophyll-like graphene is located in the mesophyll-like area 2, and the components are arranged in the heat collection area 3. The forest-like graphene area collects light energy and cooperates with the mesophyll-like graphene area to convert the collected light energy into heat energy, and the peripheral temperature of the entire component will not change drastically during the light-to-heat conversion process; the forest-like graphene area and the mesophyll-like graphene area then cooperate to transfer the heat energy to the heat collection area 3 for energy utilization such as thermoelectric conversion. In this way, the distribution of each functional area can effectively utilize the energy in a graded manner, and its temperature field only changes in the heat collection area 3, and the temperature in the forest-like area 1 and the mesophyll-like area 2 is evenly distributed, meeting the requirements of the original design.
[0062] For the forest-like area 1, the laser power is set to 4W, the laser scanning speed is set to 96mm / s, and the laser scanning spacing is set to 0.01mm; for the mesophyll-like area 2, the laser power is set to 5W, the laser scanning speed is set to 77mm / s, and the laser scanning spacing is set to 0.01mm. The laser power, scanning speed, and scanning spacing are closely related to the energy density. If the energy density is too low, the graphene is incomplete and an effective three-dimensional graphene structure cannot be formed; if the energy density is too high, the graphite is knocked off or damaged. The shape of graphene is directly related to the size of the energy density. If the energy density is too low, the laser scratching depth is not enough and effective graphene cannot be formed. If the energy density is too high, the graphene will be over-scratched, causing the graphene to be knocked off. Setting the above processing parameters can ensure that the microstructure of the graphene reaches the structural state required by the technical solution while the quality is the best.
[0063] In step S1, an organic solvent is used to help the benzoxazine monomer structure precipitate, and the organic solvent is one of petroleum ether, n-hexane and cyclohexane; when the organic solvent is added to the solution after the reaction, due to the difference in solubility between the organic solvent and xylene and the interaction with the benzoxazine monomer, the polarity and dissolution environment of the solution will be changed, and the solubility of the benzoxazine monomer in this new mixed solvent system will be reduced, so that the benzoxazine monomer will precipitate in the form of a precipitate.
[0064] Preferably, the organic solvent is petroleum ether, which can effectively reduce the generation of new impurities.
[0065] Furthermore, in step S3, the polybenzoxazine film is subjected to laser induction, and the laser wavelength is set to 280-3500 nanometers and the defocus is 6 mm.
[0066] Specifically, when lasers of different wavelengths act on graphene, different degrees of defects will be generated due to the different interactions between the photon energy and the bond energy of carbon atoms in graphene. For example, the wavelength of ultraviolet laser is shorter and the photon energy is higher. When interacting with graphene, it is easy to break the chemical bonds between carbon atoms, destroy the crystal structure of graphene, and produce more defects, thereby changing the electrical and mechanical properties of graphene. Infrared laser photon energy is lower, and the damage to the graphene structure is relatively small. Therefore, the purpose of selecting ultraviolet laser is to produce more defects and form a graphene microstructure that meets the requirements of plant leaf mesophyll and forest-like.
[0067] Furthermore, the laser wavelength directly affects the processing accuracy. The shorter the wavelength, the smaller the focused spot during processing, and the higher the processing accuracy. If the wavelength is too long and the spot is too large, the graphene area that has been laser-induced processed will be repeatedly scanned, the graphene will be excessively ablated, and the structure may be damaged. Therefore, the preferred laser wavelength range is 280-3500 nanometers. Within this range, the required graphene structure can be effectively formed while ensuring that the processed area is not damaged.
[0068] In addition, for laser induced processing, the defocus is set to 6 mm. The defocus is related to the energy density per unit area. When the defocus is set to 6 mm, graphene can be completely formed to form an effective three-dimensional graphene structure without damaging the graphene. The quality of the graphene processed under this defocus is better.
[0069] Preferably, in step S1, the phenol source is bisphenol A, and the molar mass ratio of bisphenol A: 4,4'-diaminodiphenylmethane: paraformaldehyde is (1-1.2): (0.8-1.2): (1-1.5);
[0070] The heating temperature was 120°C and the stirring time was 6 h.
[0071] Specifically, in step S1, the phenol source, amine source and polyformaldehyde react. If the temperature is too low, the thermal motion of the molecules is not intense enough, the effective collision frequency between the reactant molecules is low, the reaction rate will be very slow, and the reaction will be difficult to fully proceed. If the temperature is too high, some side reactions may be induced, such as decomposition or over-polymerization of the reactants, which will affect the yield and quality of the polybenzoxazine monomer. When the heating temperature is 120°C, stirring can maximize the yield of the polybenzoxazine monomer.
[0072] In addition, if there is no stirring or the stirring time is insufficient, the temperature will be uneven, resulting in inconsistent reaction rates, which may cause side reactions, such as decomposition of reactants in areas where the temperature is too high. Stirring can keep the temperature of the entire reaction system relatively consistent, and it can be carried out stably at the set temperature of 120°C. At the same time, the stirring time is 6 hours to ensure complete reaction.
[0073] Preferably, in step S2, the heating temperature for melting the benzoxazine monomer is 110° C., and the degassing time is 30 min.
[0074] It is worth noting that benzoxazine monomer has a certain melting point, and the temperature of 110°C can fully melt the benzoxazine monomer. At this temperature, the benzoxazine monomer changes from solid to liquid, completely melts, and increases fluidity, which is convenient for subsequent operations, ensures the smooth filling process, and ensures the molding quality of the polybenzoxazine film. At the same time, it minimizes the decomposition or premature polymerization of the monomer caused by excessive temperature, ensuring the quality of the obtained thermal conductive composite material.
[0075] At the same time, the degassing time is limited to 30 minutes to remove all gases to the maximum extent, thereby increasing the probability of achieving the desired effect and reducing the impact of residual bubbles on the optical and mechanical properties of the film; and avoiding increasing the production cycle and cost, as well as some unnecessary changes, such as partial oxidation of benzoxazine monomers due to excessive time, to ensure the degassing effect while taking into account both production efficiency and the quality of the polybenzoxazine film.
[0076] Preferably, in step S2, the polybenzoxazine fluid is cured at high temperature, first at 180°C for 2 hours, then at 200°C for 2 hours, and finally at 220°C for 2 hours.
[0077] Specifically, the polycondensation reaction of benzoxazine monomer is a heat-induced polymerization reaction, so temperature is an important factor affecting the polycondensation reaction and the quality of the generated benzoxazine monomer. At lower temperatures, the thermal motion of the monomer molecules is relatively slow, the reaction activity is low, and the polymerization reaction is difficult to proceed effectively; at too high a temperature, the reaction rate may be too fast, resulting in too many side reactions, such as monomer decomposition, excessive cross-linking, etc., affecting the quality of the polybenzoxazine film. 180°C is a temperature that can effectively initiate the polymerization reaction of benzoxazine monomer. At this temperature, the benzoxazine monomer molecules obtain enough energy to enable the polycondensation reaction between the phenolic hydroxyl group and the amino group to start at an appropriate rate. At this time, the reaction is relatively mild, and the polymer chain can be gradually constructed, which is conducive to the formation of a more regular polymer structure.
[0078] Then, the temperature is raised to 200°C to further accelerate the rate of the polymerization reaction. At this temperature, the activity of the benzoxazine monomer is higher, and the frequency of intermolecular collisions increases, which can enable more phenolic hydroxyl groups and amino groups to react, promote the growth and cross-linking of polymer chains, and help improve the mechanical properties of the polybenzoxazine film, making it denser and more stable.
[0079] Finally, the film was cured at 220°C. The performance of the polybenzoxazine film was further optimized at a higher temperature. At this temperature, the polymerization reaction was more complete, which could make the cross-linking density of the polybenzoxazine film higher, thereby enhancing the toughness and wear resistance of the polybenzoxazine film. At the same time, the higher temperature helped to remove the small molecules that might remain inside the polybenzoxazine film, such as the unreacted monomers and the small molecule byproducts generated during the reaction, and improved the purity and quality of the film.
[0080] At the same time, the 2-hour curing time at each temperature ensures that the polymerization reaction is sufficient at the corresponding temperature to achieve the expected performance improvement effect without increasing production costs and production cycles.
[0081] Preferably, in step S1, the step of purifying to obtain the benzoxazine monomer is:
[0082] A. Dissolving: dissolving the precipitated benzoxazine monomer structure in a solvent to obtain a solution containing the benzoxazine monomer; the solvent is one of ethyl acetate, dichloromethane and chloroform;
[0083] B. Washing: Wash the solution containing benzoxazine monomer three times with deionized water;
[0084] C. Drying: After the washed solution containing the benzoxazine monomer is dried using anhydrous sodium sulfate or anhydrous magnesium sulfate, a rotary evaporator is used to obtain the benzoxazine monomer.
[0085] In this purification step, the yield of the obtained benzoxazine monomer after purification is ensured to be 90%, and the loss is reduced. Among them, because the purification needs to be washed with deionized water, the deionized water is adsorbed with the anhydrous sodium sulfate or anhydrous magnesium sulfate. The rotary evaporator can evaporate efficiently, heat gently, and effectively separate the solvent, which is conducive to improving the purity of the obtained benzoxazine monomer.
[0086] Preferably, in step S4, the processed three-dimensional laser-induced graphene is immersed in molten PEG, the filling time is 2 hours, and the temperature is 90°C.
[0087] It is worth noting that in this step, the purpose is to fill PEG into the mesophyll-like graphene area, but because in a vacuum environment, liquid PEG will penetrate into all accessible spaces as much as possible under the action of the internal and external pressure difference, so it will also enter the forest-like graphene area, which can further improve the performance of the prepared thermal conductive composite material. First, PEG plays a bonding role. After the pores and gaps originally existing between the two graphenes with different microstructures are filled with PEG, the internal spatial structure of the graphene will become tighter. From a microscopic point of view, the gaps of the graphene in the forest-like graphene area are filled, specifically the roots of the forest community are filled, which will make the connection between the originally relatively independent structural units become closer, and further improve the heat conduction efficiency. Secondly, the morphology of the graphene in the forest-like graphene area is similar to the forest community structure of northern coniferous forests such as pine trees, in which light absorption and light energy conversion occur in branches and leaves with topological structures, so the gaps between the branches and leaves are relatively large without the gaps at the roots of the forest community, and even if a trace amount of PEG is filled and immersed, it will not have a great impact on light absorption and light-heat conversion. Finally, the PEG filled into the forest-like graphene region can maintain temperature balance, ensuring that the graphene structure will not change due to temperature changes.
[0088] In summary, in step S4, the processed 3D laser-induced graphene is immersed in molten PEG with a filling time of 2 h and a temperature of 90 °C, ensuring that PEG effectively fills the mesophyll-like graphene region while not affecting the role of the forest-like graphene region and further improving the performance.
[0089] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0090] Example Group
[0091] Example 1
[0092] S1. Preparation of benzoxazine monomer: 0.525 mol of bisphenol A, 0.477 mol of 4,4'-diaminodiphenylmethane, 0.716 mol of polyformaldehyde and 500 ml of xylene were mixed, heated to 120° C. and stirred for 6 hours, and after the solution was cooled, 2000 ml of petroleum ether was added dropwise to precipitate; the precipitate was dissolved in 400 ml of ethyl acetate, washed three times with deionized water, filtered with anhydrous sodium sulfate and dried, and then a rotary evaporator was used to obtain a benzoxazine monomer;
[0093] S2, preparing a polybenzoxazine film: melting a benzoxazine monomer and degassing for 30 minutes, setting the temperature at 110° C. to obtain a PH-ddm fluid, pouring the PH-ddm fluid into a glass mold, curing at 180° C., 200° C. and 220° C. for 2 hours respectively, and demolding after cooling to obtain a polybenzoxazine film;
[0094] S3, laser induced processing: fix the polybenzoxazine film on the processing platform, use ultraviolet laser, according to the preset pattern, for the forest-like area 1, set the laser power to 4W, the laser scanning speed to 96mm / s, and the laser scanning spacing to 0.01mm; for the mesophyll-like area 2, set the laser power to 5W, the laser scanning speed to 77mm / s, and the laser scanning spacing to 0.01mm; obtain the processed three-dimensional laser induced graphene;
[0095] The graph includes a forest-like region 1, a mesophyll-like region 2 and a heat collection region 3, and the area ratio of the forest-like region 1 to the mesophyll-like region 2 is 1:3;
[0096] S4. Filling PEG: Immersing the processed three-dimensional laser-induced graphene into molten PEG, and after vacuum treatment, removing excess PEG on the surface to obtain a thermally conductive composite material based on laser-induced graphene.
[0097] Comparative group
[0098] Comparative Example 1
[0099] Compared with Example 1, when comparative example 1 is subjected to laser induction, in its preset graph, the area ratio of the forest-like region 1 to the mesophyll-like region 2 is 1:1, and other aspects are the same.
[0100] Comparative Example 2
[0101] Compared with Example 1, when comparative example 2 is subjected to laser induction, its preset pattern does not include the mesophyll-like region 2, and other aspects are the same.
[0102] Comparative Example 3
[0103] Compared with Example 1, when comparative example 3 is subjected to laser induction, its preset pattern does not include the forest-like area 1, and other aspects are the same.
[0104] The thermally conductive composite materials based on laser-induced graphene prepared in the above examples and comparative examples were subjected to performance tests, and the specific performance tests were as follows:
[0105] Light absorption rate: The light absorption rate is calculated by simulating solar radiation under the AM1.5 standard and in the wavelength range of 280-2500 nanometers.
[0106] Temperature rise rate: Under the AM1.5 standard, simulate solar radiation, and at room temperature of 25°C, test the temperature after 5s, 40s and 60s to obtain the temperature rise rate.
[0107] The specific test results are shown in Table 1:
[0108] Table 1 Test results of relevant properties of thermal conductive composite materials
[0109] Performance test items Light Absorption T1 / ℃(t=5s) T2 / ℃(t=40s) △T1 / ℃ △T2 / ℃ Example 1 97.70% 53.8 90 65 36.2 Comparative Example 1 88.40% 50.6 88.9 63.9 38.3 Comparative Example 2 98.80% 49 86.8 61.8 37.8 Comparative Example 3 80.50% 47.3 83 58 35.7
[0110] When testing the temperature rise rate, the temperature after 60s of irradiation is basically the same as the temperature after 40s of irradiation, indicating that the equilibrium temperature has been reached at 40s. Among them, △T1 is the difference between the equilibrium temperature and the room temperature, and △T2 is the difference between the temperature at 40s and the temperature at 5s.
[0111] From the test results in Table 1, it can be seen that the light absorption rate of Example 1 is 97.70%, which is relatively high, and ΔT1 is 65°C, the temperature difference is large, and ΔT2 is small, which means that the thermal conductive composite material obtained in Example 1 has the highest light-to-heat conversion efficiency, and the fluctuation amplitude at high temperature is small. It has a high light absorption rate and a high light-to-heat conversion efficiency.
[0112] In Comparative Example 1, the ratio of the area occupied by the forest-like graphene to the area occupied by the mesophyll-like graphene is 1:1. At this ratio, the light absorption rate is 88.40%, which is significantly lower than 97.70% in Example 1. Although the temperature difference is 63.9°C, which is a relatively high temperature difference, the temperature rise rate is slow, and △T2 is 38.3°C, which is greater than 36.2°C in Example 1. The fluctuation range is large at high temperatures, which is not conducive to light absorption and has an impact on components.
[0113] In Comparative Example 2, mesophyll-like graphene is not included, and the obtained thermally conductive composite material has a large area of forest-like graphene, so the light absorption rate is very high, which is 98.80%, which is greater than 97.70% in Example 1, but the temperature difference of Comparative Example 2 is 61.8°C, which is less than 65°C in Example 1, indicating that Comparative Example 2 has a good light absorption rate, but the light-to-heat conversion rate is insufficient, and it is impossible to have a good light absorption rate and a good light-to-heat conversion efficiency at the same time.
[0114] Comparative Example 3 does not include forest-like graphene, and the resulting thermally conductive composite material has the lowest light absorption rate, which is only 80.50%, much lower than 97.70% in Example 1. At the same time, the temperature difference between the equilibrium temperature and the room temperature is the smallest, which is only 58°C, lower than 65°C in Example 1. This shows that although the thermally conductive composite material made of only mesophyll-like graphene has good temperature stability, its light absorption rate and light-to-heat conversion rate are not as good as those in Example 1.
[0115] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.
Claims
1. A thermally conductive composite material based on laser-induced graphene, characterized in that: It comprises a resin support layer and a graphene layer, wherein the resin support layer is a polybenzoxazine film; The graphene layer is obtained by laser induced processing on the resin support layer, the graphene layer includes a forest-like graphene region and a mesophyll-like graphene region, and the ratio of the area of the forest-like graphene region to the mesophyll-like graphene region is 1:3; The forest-like graphene region and the mesophyll-like graphene region are each composed of a plurality of wedge-shaped partitions, and the wedge-shaped partitions of the forest-like graphene region and the wedge-shaped partitions of the mesophyll-like graphene region are distributed at intervals; The graphene layer is filled with a phase change material, and the phase change material is PEG.
2. The thermally conductive composite material based on laser-induced graphene according to claim 1, characterized in that: The forest-like graphene region and the mesophyll-like graphene region form a ring; The wedge angle A of the wedge-shaped partition of the forest-like graphene region is 11.25°.
3. The thermally conductive composite material based on laser-induced graphene according to claim 1, characterized in that: The ratio of the thickness of the resin support layer to the thickness of the graphene layer is 7:
3.
4. A method for preparing a thermally conductive composite material based on laser-induced graphene, characterized in that: The method for preparing a thermally conductive composite material based on laser-induced graphene according to any one of claims 1 to 3 comprises the following steps: S1. Preparation of benzoxazine monomer: using a phenol source, an amine source and polyformaldehyde as raw materials, and xylene as a solvent, heating and stirring, synthesizing a benzoxazine monomer structure, and then using an organic solvent to help the benzoxazine monomer structure precipitate, and purifying to obtain a benzoxazine monomer; wherein the phenol source is one of bisphenol A and phenol, the amine source is 4,4'-diaminodiphenylmethane, and the organic solvent is one of petroleum ether, n-hexane and cyclohexane; S2, preparing a polybenzoxazine film: melting and degassing a benzoxazine monomer to obtain a polybenzoxazine fluid, pouring the polybenzoxazine fluid into a glass mold, curing at high temperature, and demolding after cooling to obtain a polybenzoxazine film; S3, laser induced processing: fix the polybenzoxazine film on the processing platform, use an ultraviolet laser, according to a preset pattern, laser induce the corresponding processing area on the polybenzoxazine film, and obtain the processed three-dimensional laser induced graphene; The graph includes a forest-like region, a mesophyll-like region and a heat collection region; the forest-like graphene region corresponds to the forest-like region, and the mesophyll-like graphene region corresponds to the mesophyll-like region; For the forest-like area, the laser power was set to 4 W, the laser scanning speed was set to 96 mm / s, and the laser scanning spacing was set to 0.01 mm; for the mesophyll-like area 2, the laser power was set to 5 W, the laser scanning speed was set to 77 mm / s, and the laser scanning spacing was set to 0.01 mm; S4. Filling PEG: Immersing the processed three-dimensional laser-induced graphene into molten PEG, and after vacuum treatment, removing excess PEG on the surface to obtain a thermally conductive composite material based on laser-induced graphene.
5. The method for preparing a thermally conductive composite material based on laser-induced graphene according to claim 4, characterized in that: In step S3, the polybenzoxazine film is subjected to laser induction, and the laser wavelength is set to 280-3500 nanometers and the defocus amount is 6 mm.
6. The method for preparing a thermally conductive composite material based on laser-induced graphene according to claim 4, characterized in that: In step S1, the phenol source is bisphenol A, and the molar mass ratio of bisphenol A: 4,4'-diaminodiphenylmethane: paraformaldehyde is (1-1.2): (0.8-1.2): (1-1.5); The heating temperature was 120°C and the stirring time was 6 h.
7. The method for preparing a thermally conductive composite material based on laser-induced graphene according to claim 4, characterized in that: In step S2, the heating temperature for melting the benzoxazine monomer is 110° C., and the degassing time is 30 minutes.
8. The method for preparing a thermally conductive composite material based on laser-induced graphene according to claim 4, characterized in that: In step S2, the polybenzoxazine fluid is cured at high temperature, first at 180°C for 2 hours, then at 200°C for 2 hours, and finally at 220°C for 2 hours.
9. The method for preparing a thermally conductive composite material based on laser-induced graphene according to claim 4, characterized in that: In step S1, the steps of purifying and obtaining the benzoxazine monomer are: A. Dissolving: dissolving the precipitated benzoxazine monomer structure in a solvent to obtain a solution containing the benzoxazine monomer; the solvent is one of ethyl acetate, dichloromethane and chloroform; B. Washing: Wash the solution containing benzoxazine monomer three times with deionized water; C. Drying: After the washed solution containing the benzoxazine monomer is dried using anhydrous sodium sulfate or anhydrous magnesium sulfate, a rotary evaporator is used to obtain the benzoxazine monomer.
10. The method for preparing a thermally conductive composite material based on laser-induced graphene according to claim 4, characterized in that: In step S4, the processed three-dimensional laser-induced graphene is immersed in melted PEG, the filling time is 2 hours, and the temperature is 90°C.
Citation Information
Patent Citations
Infrared camouflage polyimide composite film with all-weather scene and preparation method
CN118994716A
Heating device
WO2024173793A1